Level and Associated Factors of Literacy and Stigma of Suicide among Bangladeshi Physicians: A Cross-Sectional Assessment - Mohammad Muntasir Maruf; Farzana Rabin Shormi; Mohammad Waliul Hasnat Sajib; Panchanan Acharjee; Hosnea Ara; Susmita Roy; Srijony Ahmed; S. M. Yasir Arafat (Mental Illness)
Objectives. Literacy and stigma of suicide among doctors affect health-service delivery for persons with suicidal behavior. However, no attempt has been identified to assess those among physicians in Bangladesh. We aimed to determine the level and associated factors of suicide literacy and stigma toward suicide among physicians in Bangladesh. Methods. We collected data from 203 physicians in February 2022 by Google Forms. We used the Bangla literacy of suicide scale (LOSS-B) and the Bangla stigma of suicide scale (SOSS-B) to assess the literacy and stigma of suicide. The instrument also included questions for collecting sociodemographic variables and assessing suicidal behavior. Results. The mean age of the physicians was 34.17±7.86 (range 23–66) years, 109 (53.7%) were females, 150 (73.9%) were married, and 181 (89.2%) were Muslim. The mean LOSS-B score was 5.9±1.96 (range 1-10). Suicide literacy was higher in singles (p=0.013), doctors with a family history of suicide (p=0.018), a history of suicidal thought in lifetime (p≤0.001), and in the last year (p=0.03). Muslims (p=0.017) and city dwellers (p=0.021) had higher scores in the stigma subscale of SOSS-B whilst respondents with history of mental illness had a significantly lower level of stigma (p≤0.006). The stigma and isolation subscales were positively correlated indicating a higher value stigma creates higher isolation (p≤0.001). No relationship between suicide literacy and suicide stigma was identified among the physicians. Conclusions. Suicide literacy among the physicians of Bangladesh is low albeit higher than the level among the students. Appropriate programs should be designed to improve the status quo because physicians play fundamental roles as health-service providers as well as gatekeepers in suicide prevention.